Comparative Evaluation of Speaking and Writing Skills in Project Level 1 (4th Edition) and Achievers A1+ - Min, Lee Sun; Floris, Flora Debora (IJET (Indonesian Journal of English Teaching), 2017)
This study is intended to find out about the two basic skills which are speaking and writing skill presented in Project level 1 (4th edition) and Achievers A1+ textbook. The textbooks were evaluated by using the theoretical framework as proposed by Cunningsworth (1995). 4 criteria were used to evaluate the presentation of the speaking skill and 9 criteria were used to examine the writing sections. The findings of this study show some interesting similarities and differences that both textbooks have on the presentation of speaking and writing skills.